Study on the Effect of Pharmaceutical Excipient PEG400 on the Pharmacokinetics of Baicalin in Cells Based on MRP2, MRP3, and BCRP Efflux Transporters - Dan Yang; Min Zhang; Mei Zhao; Chaoji Li; Leyuan Shang; Shuo Zhang; Pengjiao Wang; Xiuli Gao (MDPI AG, 2024)
Pharmaceutical excipient PEG400 is a common component of traditional Chinese medicine compound preparations. Studies have demonstrated that pharmaceutical excipients can directly or indirectly influence the disposition process of active drugs in vivo, thereby affecting the bioavailability of drugs. In order to reveal the pharmacokinetic effect of PEG400 on baicalin in hepatocytes and its mechanism, the present study first started with the effect of PEG400 on the metabolic disposition of baicalin at the hepatocyte level, and then the effect of PEG400 on the protein expression of baicalin-related transporters (BCRP, MRP2, and MRP3) was investigated by using western blot; the effect of MDCKII-BCRP, MDCKII-BCRP, MRP2, and MRP3 was investigated by using MDCKII-BCRP, MDCKII-MRP2, and MDCKII-MRP3 cell monolayer models, and membrane vesicles overexpressing specific transporter proteins (BCRP, MRP2, and MRP3), combined with the exocytosis of transporter-specific inhibitors, were used to study the effects of PEG400 on the transporters in order to explore the possible mechanisms of its action. The results demonstrated that PEG400 significantly influenced the concentration of baicalin in hepatocytes, and the AUC0-t of baicalin increased from 75.96 ± 2.57 μg·h/mL to 106.94 ± 2.22 μg·h/mL, 111.97 ± 3.98 μg·h/mL, and 130.42 ± 5.26 μg·h/mL (p ˂ 0.05). Furthermore, the efflux rate of baicalin was significantly reduced in the vesicular transport assay and the MDCKII cell model transport assay, which indicated that PEG400 had a significant inhibitory effect on the corresponding transporters. In conclusion, PEG400 can improve the bioavailability of baicalin to some extent by affecting the efflux transporters and thus the metabolic disposition of baicalin in the liver.